Intravesical Colistin Bladder Irrigation for Multidrug Resistant Urinary Tract Infections in Critically Ill Patients with Renal Compromise: A Single-Center Case Series from Nepal - Poudel, Saroj; Khadka, Bikash; Khanal, Kishor; Ghimire, Anup; Regmi, Ashim (Journal of Nepalese Society of Critical Care Medicine, 2026)
Multidrug-resistant (MDR) gram-negative infections are increasing, posing a challenge in critically ill patients with renal impairment. Intravesical colistin irrigation offers targeted therapy while minimizing systemic toxicity. We present three critically ill patients with renal compromise and MDR urinary tract infections (UTIs) caused by Klebsiella pneumoniae, Acinetobacter spp., and Pseudomonas aeruginosa. All patients received intravesical colistimethate sodium (1 million units in 100 ml saline, 8-hourly for 7 days). Clinical resolution occurred within 48 hours, with negative urine cultures post-treatment and no adverse effects. Intravesical colistin irrigation serves as a valuable treatment alternative for managing MDR UTIs in renally compromised patients, minimizing systemic toxicity. Further studies are needed to optimize dosing and assess long-term safety.